Labour exploitation in human trafficking law - Weatherburn, Amy (Human rights research series, 2021)
"The 2000 Protocol to Prevent, Suppress and Punish Trafficking in Persons Especially Women and Children, supplementing the United Nations (UN) Convention against Transnational Organized Crime, is a noteworthy achievement and, crucially, provides the first internationally agreed definition of the human trafficking. However, it fails to provide clarity as to the exact scope and meaning of exploitation. Instead, it provides an open-ended list of forms of exploitation that “at a minimum” amount to exploitation. The international definition’s preference for an enumerative approach has subsequently been replicated in most regional and domestic legal instruments. In the absence of a clear definition of exploitation, it is difficult to draw the line between labour exploitation in terms of violations of labour rights and extreme forms of exploitation such as those listed in the UN Protocol; namely, forced or compulsory labour, practices similar to slavery and slavery. This book addresses this legal gap by seeking to conceptualise labour exploitation in criminal law. The book uses exploitation theory to understand its application in law. The legal and theoretical analysis of exploitation first identifies the foundational elements of exploitation and then applies them to a comparative, empirical, domestic criminal case law analysis of two European national legal orders: Belgium and England & Wales. The book concludes with a proposition for a legal conceptualisation of labour exploitation that identifies the necessary and sufficient conditions that are required to determine whether or not the involuntary provision of work or services amounts to labour exploitation. The book’s presentation of an evidence-based conceptualisation of labour exploitation is not only of added value for scholars but also for legal practitioners, policy makers and civil society representatives who are required to interpret and apply human trafficking law policy and practice in order to determine the existence (or not) of exploitative working conditions." --